Georges Perec and Nouveau Roman. On the Zones of Intersections and Divergencies with Alain Robbe-Grillet’s Works - Vladislav V. Kirichenko (Studia Litterarum)
The article examines intertextual links between the works of the French writers Georges Perec and Alain Robbe-Grillet. Not only early texts by Perec but also further ones in form and content refer to the artistic discoveries and inventions of the representatives of Nouveau Roman. In the modern history of French literature, Perec usually appears as an antipode of the Nouveau Roman approach to writing; nevertheless, it is relevant to see and analyze the places of these discrepancies to understand better the specifics and creativity of Perec and the characteristics of the representatives of the Nouveau Roman. The study focuses on early texts (Les Choses, Un homme qui dort), which reveal direct links with the poetics of the nouveau roman, Alain Robbe-Grillet in particular, and on later ones (La Disparition). The article concludes with the significance of the typological links between Nouveau Roman and Perec’s early work, as well as their significant dissimilarity, which consists of subsequent authorial aspirations and attitudes towards style and writing ideas.